Neuroprotective effects of morroniside from Cornus officinalis sieb. Et zucc against Parkinson's disease via inhibiting oxidative stress and ferroptosis - Mao Li; Junli Zhang; Lianyan Jiang; Wujun Wang; Xianrong Feng; Meijun Liu; Dongdong Yang (BMC, 2023)
Abstract Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer disease accompanied by the death of dopaminergic neurons and brain nigrostriatal mitochondrial damage in the elderly population. The features of the disease include tremor, rigidity, postural instability, and motor retardation. The pathogenesis of Parkinson's disease is complex, and abnormal lipid metabolism resulting in ferroptosis due to the excessive accumulation of free radicals from oxidative stress in the substantia nigra of the brain was thought to be one of the factors causing the disease. Morroniside has been reported to have significant neuroprotective effects, although it has not been studied in PD. Therefore, this study focused on determining the neuroprotective effects of morroniside (25, 50, and 100 mg/kg) on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP, 30 mg/kg)-induced mice models of PD and explored 1-methyl-4-phenylpyridinium MPP+-induced ferroptosis in PC12 cells. Morroniside restored impaired motor function in the PD mice models while reducing neuronal injury. The activation of nuclear factor erythroid 2-related factor 2/antioxidant response elements (Nrf2/ARE) by morroniside promoted antioxidation, the content of reducing agent glutathione (GSH) increased, and the level of the lipid metabolite malondialdehyde (MDA) decreased. Notably, morroniside inhibited ferroptosis in substantia nigra of the brain and PC12 cells, reduced iron levels, and upregulated the expression of the iron-regulated proteins glutathione peroxidase 4 (GPX4), solute carrier family 7 member 11 (SLC7A11), ferritin heavy chain 1 (FTH-1), and ferroportin (FPN). More importantly, morroniside repaired the mitochondrial damage, restored the mitochondrial respiratory chain, and inhibited the production of reactive oxygen species (ROS). These data indicated that morroniside could activate the Nrf2/ARE signaling pathway to increase the antioxidant capacity, thereby inhibiting abnormal lipid metabolism and protecting dopaminergic neurons from ferroptosis in PD.